Tortosa, 1936-1939 : mentalitats, revolució i Guerra Civil / per Xavier Pujadas i Martí - Pujadas i Martí, Xavier (Dertosa; 29 Publicacions d'Instituto d'Estudis Dertosensenses; 2)
Bibliografía: p. 315-323